Integrated Energy Management and Its Impact on Financial Perfor‑ mance: Evidence from the National Plastics Company - Sassi, Sara; Khalifa, Jihène (New Energy Exploitation and Application, 2025)
This study examines the impact of implementing the ISO 50001 Energy Management System (EnMS) at the National Plastics Company (CNP), a leading Tunisian manufacturer in the plastics sector. The purpose of the study is to evaluate how ISO 50001 adoption affects energy efϐiciency, ϐinancial performance, and sustainability outcomes in an energy‑intensive industrial environment. A qualitative case study approach was employed, supported by internal company data covering the period 2020–2023. The analysis used a pre‑ and post‑comparison design, with key performance indicators (KPIs) including energy consumption (kWh/kg), energy cost (DT/kg), and waste reduction (tonnes). Real‑time data visualization was achieved through Power BI dashboards. The results indicate that ISO 50001 implementation led to measurable improvements across all KPIs. Energy consumption per kilogram of production decreased steadily, and energy costs were better controlled despite market volatility. Waste reduction improved signiϐicantly, with over 72,000 kg of material saved in 2023. These outcomes demonstrate that ISO 50001 is not only an effective environmental management tool, but also a strategic driver of financial and operational performance. The study contributes to the literature by providing empirical evidence from Tunisia’s industrial sector and by highlighting the value of digital analytics in energy management. It also identifies opportunities for future research, including the use of econometric modeling and multi‑firm comparative analysis to further validate the findings.